Determinants of Social Security Participation among Informal Sector Workers: A Case Study of Rickshaw Drivers - Farah Alfia Fitri; Jusna Ahmad; Laksmyn Kadir (Indonesian Journal of Global Health Research, 2026)
Participation of informal sector workers in the Indonesian Social Security Employment Program (BPJS Ketenagakerjaan) in Gorontalo City remains low. This condition is influenced by multiple factors, including individual characteristics, occupational conditions, and socio-economic status. Understanding these determinants is essential to improve coverage and protection for informal workers. This study aimed to identify the key factors associated with BPJS Ketenagakerjaan participation among informal sector workers, particularly rickshaw drivers. This analytical observational study employed a cross-sectional design involving 342 informal sector workers selected through accidental sampling. Data were collected using structured questionnaires that had undergone validity testing using item–total correlations (items accepted when r-count > r-table, p < 0.05) and reliability testing using Cronbach’s Alpha, with coefficients ≥ 0.70 indicating acceptable internal consistency. Data were analyzed through univariate analysis, bivariate binary logistic regression, and multivariate binary logistic regression to identify significant predictors of BPJS Ketenagakerjaan participation. Bivariate analysis revealed that income, occupation, and perceptions of BPJS benefits were significantly associated with program participation. Multivariate logistic regression identified income as the most dominant predictor. The final regression model demonstrated good predictive ability, as indicated by satisfactory values of Nagelkerke R² and classification accuracy. Participation in BPJS Ketenagakerjaan among informal sector workers is influenced by various internal and external factors, with income emerging as the primary determinant. Efforts to increase participation should prioritize strategies that address these key influencing factors, particularly socio-economic barriers.